Imaging in chronic pancreatitis: State of the art review - Kamat, Rohan; Gupta, Pankaj; Rana, Surinder (Indian Journal of Radiology and Imaging, 2019)
Chronic pancreatitis (CP) is an important gastrointestinal cause of morbidity worldwide. It can severely impair the quality of life besides life-threatening acute and long-term complications. Pain and pancreatic exocrine insufficiency (leading to malnutrition) impact the quality of life. Acute complications include pseudocysts, pancreatic ascites, and vascular complications. Long-term complications are diabetes mellitus and pancreatic cancer. Early diagnosis of CP is crucial to alter the natural course of the disease. However, majority of the cases are diagnosed in the advanced stage. The role of various imaging techniques in the diagnosis of CP is discussed in this review.
Keywords: Chronic pancreatitis; diagnosis; imaging